2007
DOI: 10.1177/09603271060080076
|View full text |Cite
|
Sign up to set email alerts
|

Predicting outcomes in organophosphate poisoning based on APACHE II and modified APACHE II scores

Abstract: The aim of this study was to evaluate the scores of the Acute Physiology and Chronic Health Evaluation (APACHE) II and a modified APACHE II system (MAS), without parameters of biochemical tests; and to find prognostic value of individual elements of the APACHE II and MAS in predicting outcomes in organophosphate (OP) poisoning. Data were collected from 131 patients. The median (25th—75th percentiles) of APACHE II score for survivors without intubation were found to be lower than those of non survivors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 18 publications
(18 reference statements)
2
20
0
Order By: Relevance
“…The scores were however higher among the intubated patients as compared to those who survived without intubation. The significant (P < 0.001) correlation between APACHE II scores and the severity, observed in our study were similar to that observed in studies carried out by Eizadi-Mood et al 28 The poisoning severity score (PSS) is a severity grading scale adopted by the IPCS, the Commission of the European Union, and the European Association of Poison Centers and Clinical Toxicologists (IPCS/EC/EAPCCT) for grading the severity of poisoning. This scale is necessary to facilitate comparability of case data.…”
Section: Discussionsupporting
confidence: 91%
“…The scores were however higher among the intubated patients as compared to those who survived without intubation. The significant (P < 0.001) correlation between APACHE II scores and the severity, observed in our study were similar to that observed in studies carried out by Eizadi-Mood et al 28 The poisoning severity score (PSS) is a severity grading scale adopted by the IPCS, the Commission of the European Union, and the European Association of Poison Centers and Clinical Toxicologists (IPCS/EC/EAPCCT) for grading the severity of poisoning. This scale is necessary to facilitate comparability of case data.…”
Section: Discussionsupporting
confidence: 91%
“…[25][26][27] However, very few studies have looked as triage parameters as the outcome predictors for poisoning cases in emergency or these were done for single agents. [28][29][30] Our study shows significant difference in triage findings (SPO2, AVPU scale and MAP) for mortality and no mortality groups (fig 1). Similar findings were noted for triage parameters like body temperature <36 or >37°C, p <0.01, systolic blood pressure <100 or >150 mmHg, p<0.01, heart rate <35 or >120 bpm, respiratory rate <16 or >20 per minute to predict mortality of acute poisoning cases in emergency.…”
mentioning
confidence: 55%
“…In a previous study, an Acute Physiology and Chronic Health Evaluation II (APACHE II) score >26 was reported to be a poor prognostic indicator[12] and others reported that both APACHE II score and GCS <13 predicted outcome. [1920] A study by Goswamy et al stated that measurement of the s. acetylcholinesterase level is useful in predicting the prognosis in OP poisoning. [21] However, Aygun et al have reported that low levels of s. acetylcholinesterase support the diagnosis of acute OP poisoning, but were not related to clinical severity.…”
Section: Discussionmentioning
confidence: 99%